Internalisasi Nilai-Nilai Islam melalui Budaya Sekolah: Studi tentang Pembiasaan Sikap Tolong-Menolong di MTs Madrasatul Qur’an Tebuireng - Daud, Daud; Adawiya, Silmi (Muróbbî: Jurnal Ilmu Pendidikan, 2025)
School life is an integral part of the learning process that is inseparable from social interaction and communication. The attitude of mutual assistance among students appears to be an appropriate choice in fostering good social relationships. However, implementing a helping attitude among students at school is not easy; it requires the role of school culture. This study employed a qualitative method by collecting data directly from the field, specifically at MTs Madrasatul Qur’an Tebuireng Jombang. It is a descriptive study aimed at comprehensively describing phenomena occurring at school in the present or past, thereby illustrating the characteristics, traits, and patterns of such phenomena. The results showed that students at MTs Madrasatul Qur’an Tebuireng Jombang possess a high level of helping behavior. In shaping this attitude, the students' age levels were considered, as slight differences exist. The methods used to cultivate the helping attitude among students included setting a good example, habituating students through various activities to strengthen their helpfulness, offering advice when they are uncertain about what to do, and correcting them when they make mistakes.